Evaluation of Site Predilection of Alveoloplasty in Complete Denture - A Retrospective Study - Shalini Sathiyamoorthy1 , Revathi Duraisamy2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Alveoplasty is the common pre prosthetic procedure. It is done to provide a better anatomic environmentand create proper supporting structures for denture construction. The aim of the pre prosthetic surgery is toimprove the better retention and stability of complete denture. Alveoloplasty is done to improve the qualityand condition of the hard and soft oral aiding structures, so that they can provide retentive, supportful andstable dentures.The aim of the study is to evaluate the site predilection of alveoplasty procedure for completedenture.The Retrospective study was conducted in the University setting. Data were collected from thepatients who visited Dental college. We Reviewed patient records and analysed the data of 86000 patientsbetween June 2019 and March 2020, 120 patients data were included out of 86000 patients. The reportsincluded Age , Gender , anatomical site of alveoloplasty done. Records on each case were examined andtabulation of the data was done in excel sheets followed by statistical analysis using SPSS software with Chi- Square test.The results were obtained as graphs and charts. The study had a total sample of 120 subjectsout of which 52.5% were male and 46.7% were female. Carried out in a age group of 33 - 83 years. 35% ofparticipants in the age group of 55 - 65 years had undergone Alveoloplasty more when compared to otherage groups. 62% of Males underwent Alveoloplasty more when compared to females (38%). Alveoloplastywas performed more in lower arch (32.9%) when compared to other sites. Within the limitation of thestudy ,Males underwent Alveoloplasty more when compared to females. Alveoloplasty was performedpredominantly more in lower arch when compared to other sites.